Life in a flash stories - Macasaet, Rhona Lopa- (University of Santo Tomas Publishing House, 2022)
"A sweep of human experience. A few hundred words. This collection of sudden fiction. Stories quiet, lighthearted. Wistful, meditative. Melancholy, dark. A range of voices. Enlightening, engaging, entertaining. This is Life in a Flash, in twenty-eight words." --Back cover.